Learning Attitudes And Learning Outcomes In The Pastry Subject - Wannur, Nabilah Azzahra; Gusnita, Wiwik; Siregar, Juliana; Ulwan, Naseh (Universitas Negeri Padang, 2025)
This research is motivated by the low learning outcomes of students in the Pastry subject. One aspect related to this issue is the students' learning attitude. The purpose of this study is to examine the relationship between learning attitude and student learning outcomes in the Pastry subject at the Culinary Department of SMK Negeri 9 Padang. The research method used in this study is a quantitative approach with an ex post facto research design with a population of 224 twelfth-grade students in the 2024/2025 academic year. The sample was selected using simple random sampling. The instruments used include a Likert scale questionnaire, which has been tested for validity and reliability, and documentation of students' learning outcomes. The data were analyzed using the Pearson Product Moment correlation technique. The results show that both learning attitudes and learning outcomes are in the moderate category. The correlation coefficient of 0.796 indicates a strong relationship, and the hypothesis test shows that the t-count (10.84) is greater than the t-table (1.995), so the alternative hypothesis (Ha) is accepted.